La globalización económica y los derechos humanos (2013)
To analyze globalization in the light of Human Rights, confronts us with the dynamic that currently exists between the economic model of dominance and functional discourse of legitimation. We may wonder if this is the only possible relationship, if Human Rights condemned to be a justification of the macroeconomic model and whether economic globalization can only have opposite content quality of life of individuals.